10.1016/s0029-7437(09)70404-5 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: To analyze the efficacy and safety of various anticoagulation strategies/regimen used for managing thrombus or spontaneous echo contrast in the left atrial appendage. METHODS: Thrombus or spontaneous echo contrast in the left atrial appendage was detected via transesophageal echocardiography in 83 patients, most often during a stroke assessment. The chosen anticoagulants were compared, and follow-up was conducted with repeated transesophageal echocardiograms. RESULTS: Heparin and vitamin K antagonists (VKAs) were the most commonly selected treatment regimens. The initial resolution rate was approximately 30% across all treatment regimens after a follow-up of 8 ± 8 weeks (DOACs 30%, VKAs 30%, heparin 25%, p = 0.9). Continuing the same protocol or switching to a direct oral anticoagulant (DOAC) were the main alternatives when the thrombus persisted after the first echocardiographic control. An additional 22% of patients with repeated controls experienced resolution after 23 ± 14 weeks of anticoagulant treatment. Major bleeding events were observed in 3% of patients. CONCLUSION: Resolution of thrombi/echo contrasts was noted in a significant proportion of patients with our management approach, without apparent significant differences between treatment regimens (difficult to interpret due to the low number of patients under DOACs). Bleeding complications remain significant.